Impediments to women accountants' career progression in Malaysia - Zainal Abidin, Zubaidah; Penafort, Frances; Jusoff, Kamaruzaman; Marzuki, Marzlin (Canadian Center of Science and Education, 2008)
The apparent conflict between family life and an accounting career appears to be negatively impacting the retention of women in public accounting (Stockard, 1990). Typically, accounting entails long hours, travel, and a stressful business environment. For many women, these negative factors are intensified by family obligations and the pressures of striving for acceptance in a traditionally male-dominated profession. This investigation set out to directly survey women in the accounting profession regarding their perceptions of their own career barriers in their organizations. In addition, the study was intended to identify possible reasons for women accountants to leave their organizations and ways to retain them. The study was intended to develop a survey questionnaire that would quantify and measure perceptions of the glass ceiling. Following the review of a wide body of literature about “glass ceiling” this study established a conceptual model which related the impediments to career progression. This conceptual model leads to the formulation of an empirical schema and the generation of testable hypotheses. The following measurable constructs or variables were established: (1) exclusionary environment; (2) family responsibility; (3) workplace benefit; (4) job flexibility; (5) corporate policies; (6) job stress; and (7) job demand. This study has practical implications for employers in considering the needs and problems of women accountants in the work force. Alleviating key problems should help employers acquire and retain women accountants for a longer time, thereby maximizing their hiring and training investment. More importantly, dealing with these issues would help intelligent and capable women to continue a career as a professional accountant.